2021
DOI: 10.1186/s12951-020-00761-9
|View full text |Cite
|
Sign up to set email alerts
|

Redox-sensitive polymeric micelles with aggregation-induced emission for bioimaging and delivery of anticancer drugs

Abstract: Background Nano-drug delivery systems show considerable promise for effective cancer therapy. Polymeric micelles have attracted extensive attention as practical nanocarriers for target drug delivery and controlled drug delivery system, however, the distribution of micelles and the release of the drug are difficult to trace in cancer cells. Therefore, the construction of a redox-sensitive multifunctional drug delivery system for intelligent release of anticancer drugs and simultaneous diagnostic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…Loading the maximum amount of DOX into the micelles considerably altered the resulted hydrodynamic diameters ( Figure 2 d–f). A significant characteristic increase [ 53 , 54 ] in the hydrodynamic diameters for all the investigated samples in comparison to the free micelles was observed. By analyzing the histograms in Figure 2 c–e and Table S1 , it was observed that in the case of the PEG2K-PHis20 + DOX sample, the average determined hydrodynamic diameter was 172 ± 5 nm with a polydispersity of 0.23 ± 0.02, the PEG2K-PHis26 + DOX sample presented a hydrodynamic diameter of 219 ± 5 nm (polydispersity of 0.21 ± 0.03), while the PEG2K-PHis32 + DOX sample reached a hydrodynamic diameter of 290 ± 10 nm (polydispersity of 0.28 ± 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…Loading the maximum amount of DOX into the micelles considerably altered the resulted hydrodynamic diameters ( Figure 2 d–f). A significant characteristic increase [ 53 , 54 ] in the hydrodynamic diameters for all the investigated samples in comparison to the free micelles was observed. By analyzing the histograms in Figure 2 c–e and Table S1 , it was observed that in the case of the PEG2K-PHis20 + DOX sample, the average determined hydrodynamic diameter was 172 ± 5 nm with a polydispersity of 0.23 ± 0.02, the PEG2K-PHis26 + DOX sample presented a hydrodynamic diameter of 219 ± 5 nm (polydispersity of 0.21 ± 0.03), while the PEG2K-PHis32 + DOX sample reached a hydrodynamic diameter of 290 ± 10 nm (polydispersity of 0.28 ± 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…The hemolysis of Fe 3 O 4 -siPD-L1@M -BV2 was investigated by using rat erythrocytes [ 43 ]. The release of siPD-L1 from Fe 3 O 4 -siPD-L1@M -BV2 in GSH-containing solution was observed by gel retardation assay [ 44 ]. The stability of Fe 3 O 4 -siPD-L1@M -BV2 in RNase A-containing buffer was observed by gel retardation assay.…”
Section: Methodsmentioning
confidence: 99%
“…AIEgenic micelles have been widely utilized to deliver aromatic drugs in nanomedicine studies, due to the beneficial π-π and hydrophobic interactions between the drugs and the AIEgens which inhibit cargo leakage during transportation. [81,83,[167][168][169][170][171][172] In addition, AIEgenic micelles have been endowed with stimuli-responsive units to achieve controlled release when the nanoparticles reached the targeted tissue microenvironment. [43,173] For instance, Zhao et al reported AIEgenic micelles with enzyme responsive properties as drug carriers (Figure 7A).…”
Section: Drug Delivery and Theranosticsmentioning
confidence: 99%